2015
DOI: 10.1089/ars.2014.5880
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Heart Sense Changes in Oxygen Tension: A Role for Ion Channels?

Abstract: A further understanding of these cellular processes should result in interventions that assist in preventing the deleterious effects of acute changes in oxygen tension such as alterations in contractile function and cardiac arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…It has been proposed that the short NT isoform contains an “oxygen sensing region” encoded by exon 45 15 . We have previously demonstrated that hypoxia does not directly alter the function of the long NT isoform or the short NT isoform reconstituted in proteoliposomes 16 . If this is true, the channel must be responding as a “redox sensor”.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been proposed that the short NT isoform contains an “oxygen sensing region” encoded by exon 45 15 . We have previously demonstrated that hypoxia does not directly alter the function of the long NT isoform or the short NT isoform reconstituted in proteoliposomes 16 . If this is true, the channel must be responding as a “redox sensor”.…”
Section: Discussionmentioning
confidence: 95%
“…It has been proposed that the Ca v 1.2 protein contains an “oxygen sensing region” encoded by exon 45 15 . However, a direct effect of hypoxia on Ca v 1.2 function has not been demonstrated 16 . In addition, thiol reducing agents have been demonstrated to mimic the effects of hypoxia on Ca 2+ currents while thiol oxidising agents increase Ca 2+ currents or attenuate the effects of hypoxia 13 14 17 18 19 20 21 22 23 24 .…”
mentioning
confidence: 99%
“…The mechanism by which lowering PO 2 differentially regulates L-type Ca 2+ channels expressed in PASMCs is not known. It has been reported that the pore-forming subunit of L-type channels (α1C or Cav 1.2) expressed in the heart has specific cysteine residues whose oxidation could increase the probability of channel opening (Hool, 2015;Muralidharan et al, 2016). This fact would explain the increase in voltage-dependent Ca 2+ current in pulmonary resistance myocytes.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Studies performed using mutated α1C subunits with replacement of specific cysteine residues have shown that the L-type Ca 2+ channels are indeed redox sensors although the effects of ROS on these channels are a matter of controversy (Hool, 2015;Muralidharan et al, 2016). Direct modification by oxidants of thiol groups in purified L-type Ca 2+ channels reconstituted in proteoliposomes increases channel open probability, while reducing agents have the opposite effect (Hool, 2015).…”
Section: Voltage-dependent Ca 2+ Channelsmentioning
confidence: 99%
“…These authors reported PO 2 -related decreases in myocardial work and power even when oxygen levels were well above physiological and suggested that this result was due to a mechanism other than reduced energy supply. Several potential oxygen sensing mechanisms have been identified in cardiac tissue [including H 2 S, NO, ROS, and ion (Ca 2ϩ ) channels (13,23,47,55)], and it is possible that these mechanisms were more sensitive to changes in PO 2 in hypoxic-acclimated trout.…”
Section: Impact Of Acute and Chronic Hypoxia On Myocardial Work And Power Outputmentioning
confidence: 99%